Persebaran Potensi Cagar Budaya Megalithikum di Kabupaten Poso Sulawesi Tengah - Haliadi, Haliadi; Butudoka, Zubair; Djorimi, Iksam (Bomba: Jurnal Pembangunan Daerah, 2024)
The Governor of Central Sulawesi has declared that Central Sulawesi Province will have a thousand megaliths on October 10 2023 because it has the potential for Cultural Heritage (CH) in the form of megalithic stones as evidence of civilization in the Central Sulawesi Region, especially in Poso Regency. This article will focus on three valleys in Poso Regency, namely the Bada Valley, Behoa Valley and Napu Valley. The research entitled "Distribution of Potential Megalithic Cultural Heritage in Poso Regency, Central Sulawesi" aims to describe the distribution of potential cultural heritage in the form of megalithicum in the Bada Valley, Lemba Bada and Napu Valley in Poso Regency. Likewise, it also describes the existence of megaliths which are the potential of every valley in Poso Regency in the form of buho, jar lids, jar containers, scratched stones, flat stones, structures, monoliths, stone pedestals, stone mortars, trays, stone mortars, hollow stones, statues, and containers, kalamba lid, and kalamba container and other shapes. Finally, this research will analyze folklore about the community that supports megalithic civilization in Poso Regency, namely the Pekurehua community.